Increasing the overall efficiency of injection molding equipment in the plastics industry: A Lean and Industry 4.0 innovation - Rodriguez-Vasquez, Claudia; Rojas-Minaya, Sebastian; Saenz-Moron, Martin; Straujuma, Anita (LACCEI, 2025)
Organizations seek to improve their operational efficiency by addressing a key challenge in the plastics industry: low equipment efficiency, particularly in injection molding processes. This research analyzes the causes of high mold setup and disassembly times, as well as increased machine downtime due to electrical failures in the injection molding process. It also examines the high rate of defective products due to the temperature instability of the injection molding machine and its performance, which currently operates at an efficiency of only 71.68%. To address this problem, an improvement project is proposed that integrates Lean Manufacturing methodologies such as SMED, Andon, and FMEA, as well as the use of digital twins and statistical process control (SPC). The objective is to optimize the effectiveness of the injection molding machine, measured by the Overall Equipment Effectiveness (OEE) indicator, and improve the company’s competitiveness within the sector.